An Inquiry to Move an Underutilized Best Practice Forward: Barriers to Partnering in the Architecture, Engineering, and Construction Industry. Issue 1 (February 2015) - Mollaoglu, Sinem; Sparkling, Anthony; Thomas, Sean
ABSTRACT There is an obvious need in the architecture, engineering, and construction (AEC) industry for improved project team integration through project delivery to ensure improved project outcomes. The literature reports that, among other methods, project partnering, when followed successfully, provides a great opportunity to improve project performance via improved collaboration among key project stakeholders (e.g., owner, designer, contractor) and reduce claims as a result while letting all project members stay in their traditional roles and work under any contractual framework, including design‐bid‐build. Despite its potential and history in the United States since the late 1980s and being classified as one of the best practices by the Construction Industry Institute in 1996, partnering continues to be underutilized. Existing research on partnering is mostly limited to public projects such as mega roadway and bridge projects. Guided by the literature, the aim of this research is to understand and report barriers to project partnering in the United States from both vertical/horizontal and public/private construction sectors. Via a comprehensive literature review, followed by a Delphi survey of partnering experts, this study systematically classified barriers to project partnering. In study results, implementation barriers to partnering during project delivery are more frequently pronounced than the barriers to its adoption. Of the top reported barriers to project partnering, the majority are cultural; project team related barriers show the greatest area of potential for improvement; and contrary to the literature, none is legislative. The study contributes to the body of knowledge by drawing attention to project delivery and management practices in the AEC industry to improve team collaboration and chances of successful implementation and adoption of integrative practices.